Leverage and liquidity to firm value moderated by firm size: a signaling theory approach - Kartika Sari; Akhmadi Akhmadi; Wawan Ichwanuddin (Institute of Computer Science (IOCS), 2023)
This study used the Signaling Theory approach to determine the effect of leverage and liquidity on firm value and used firm size as a moderating variable. The research sample used is food and beverage sector companies listed on the Indonesia Stock Exchange during 2016-2021. Data processing was carried out with the STATA version 17 statistical application. The leverage variable is used to see the proportion of debt used by the company in its financing and the results show that leverage is proven to increase firm value significantly. Liquidity is used to see the company's ability to pay its debt obligations and the results show that liquidity is proven to significantly increase firm value. These findings strengthen the theory that leverage and liquidity have a positive effect on firm value. Firm size is used as a variable that is considered to strengthen the relationship between leverage and liquidity. However, the results show that firm size is not proven to strengthen the relationship between leverage and liquidity on firm value.